Agent Based Simulation of Student Passing through the Network of Study Duties - Jelínek, Jiří; Míková, Irena; Přibyl, Vladimír; Svoboda, Petr (Vysoká škola ekonomická v Praze, 2014)
The article deals with the one possible area of using the agent based approach to simulations. This method is advantageous for the tasks that can be modeled through the set of the basic building elements - agents and their interaction. The paper shows the application of this approach for simulation of higher education. Conceptual model of university education based on AB modeling of the students and their behavior and interactions in study processes was developed for this purpose. The aim was to develop a tool which should help to improve the processes in higher education and prevent increasing cost of study.
Multiagentní simulace průchodu studenta sutdijními povinnostmi
Keywords: Agent; Simulation; Education; Education process quality; agenti; simulace; vzdělávání; kvalita vzdělávacího procesu